The Histologic Effect of Baclofen in Rat's brain: An Experimental Study - Luma Al-Allaf; Wahda Al-Neaimy (University of Mosul, 2020)
Background: Baclofen is the only clinically available metabotropic GABAB receptor agonist. Several reports has been discussed the efficacy of baclofen but the available data on its effect of the behavior and brains' histology are still limited.Objectives: This work aims to assess the effects of long term exposure to baclofen (8weeks) on behavior and brains' histology in ratsMethods: Analysis of data of Twenty five healthy male Albino rats were performed. Rats weighing about 200–210 g with mean age of 65 days were randomly selected and categorized into three groups: Group 1(LD50 group): included five rats that gavaged with single dose of baclofen to test the LD50 of drug (145mg per Kg) .Group 2. (control group):included eight rats were gavaged with distilled water for 2 months. Group 3.(baclofen group): included 12 rats gavaged with 15mg/kg of baclofen (1/10th LD50) for 2 month. Behavioral Tests were conducted on all animals in group 2 and 3 including: Open-field test ,Open -field habituation task ,and object recognition(Novel) to examine the influence of drug on the cognition of rats. All animals were euthanized with ether after 24hours of last day of treatment. Brains were excised and collected from rats of group 2 and 3.Fixation of tissues was done using buffered solution of ten percent of formalin for twenty four hours with paraffin wax embedding. Sectioning and staining by hematoxylin and eosin protocol (H&E) and prepared to be examine histologically. To differentiate between the data of group 2 and 3 ,statistical analysis was performed by 1- way analysis of variance (ANOVA) .Least significant difference test with Duncan test was used . Value of P of equal or less than 0.05 means the difference is significant .Results: This study revealed that the rats of baclofen group traveled a greater total distance(in both sessions) when compared with those of control indicating their hyperactivity. The zone specific analysis showed that the rats that were administered with baclofen consumed markedly greater time nearby the walls in the peripheral part in the arena throughout the first and 2nd 15- min session in comparison with those of control group indicating the generalized hyperactivity and exploration. Rats of control group preferred the novel object in comparison with those of baclofen group. However there is no marked difference in the index of discrimination among rats of group 2 and 3. Histological sections of rats’ brains in group that were administered with 15mg/kg of baclofen for 2 month( baclofen group) revealed a diminished thickness in the pyramidal cells’ layer, irregular faintly stained cells with shrinkage in the some pyramidal nerve cells, dark staining cytoplasm and losing the characteristics of their nuclei.Conclusions:Chronic administration with baclofen (15mg/kg/day/2months) induces changes in the brain histology in rats, however, baclofen has no adverse effect on the behavior. To the best of our information, our work is the 1st that focus on the influence of baclofen on both the behavior and brains' histology. Our data suggesting that baclofen may have clinical utility.